2016
DOI: 10.11648/j.ajam.20160405.17
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Estimation of a DC Motor-Gear-Alternator (MGA) System via Step Response Methodology

Abstract: Mathematical models and their parameters are essential when designing controllers because they allow the designer to predict the closed loop behavior of the system. An accurate method for estimating the DC Motor-Gear-Alternator (MGA) system parameters is needed before constructing the reliable model. This paper proposed a new method of parameter estimation using Matlab/Simulink parameter estimation tool via Step Response Methodology. Optimization algorithms including the nonlinear least square, Gradient Descen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The plot in Fig. (7) shows the trajectory of the parameters at each iteration of the estimation process. It is shown that the parameters settle to their final values as the estimation process converges to a solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plot in Fig. (7) shows the trajectory of the parameters at each iteration of the estimation process. It is shown that the parameters settle to their final values as the estimation process converges to a solution.…”
Section: Resultsmentioning
confidence: 99%
“…The Simulink Parameter Estimation algorithm has inbuilt systems with ideal data which are related against the output data generated by the Simulink model [6]. By the use of optimization techniques, the software approximates the parameter and the initial conditions are stated in a way that the user-selected cost function is reduced [7]. The cost function characteristically calculates the least-square error between the model and the empirical data signals.…”
Section: Introductionmentioning
confidence: 99%